Properties of fly ash cement sand brick containing palm oil clinker as partial sand replacement - Nor Sahira, Muhamad Zam (2019)
The dumping of waste from coal industry and palm oil industry causes pollution to the environment. Palm Oil Clinker (POC) is a solid waste from palm oil industry. At the same time, the production of cement from cement industry produces various of gasses and contributes to the global warming. Besides that, it effects the human health. Excessive sand mining activity also disturbing the ecosystem like water pollution which can give effect to aquatic life and riverbank erosion. In this study, the effect of Palm Oil Clinker (POC) as partial sand replacement on compressive strength, flexural strength and water absorption of fly ash cement sand brick has been investigated. Mix consisting different percentage of Palm Oil Clinker (POC) which is 10%, 20%, 30% and 40% has been used to prepare the specimen. All specimen was water cured until the testing date. Compressive strength and flexural strength test were conducted at 7 and 28 days. All the test was conducted according to ASTM standard for brick. The findings shows that fly ash cement sand brick containing 30% of Palm Oil Clinker (POC) replacement provided the best results in terms of compressive strength and flexural strength. However, utilization of Palm Oil Clinker (POC) shows increase of water absorption.